Delphi Validation of a Pain Management E-Learning Module for Critical Care Nurses in Saudi Arabia - Almutairi, Abeer Mohammed F; Said, Faridah Mohd (Nurse Media Journal of Nursing, 2026)
Background: Critical care nurses play a central role in pain management; however, persistent knowledge and competency gaps continue to affect patient outcomes globally, including in Saudi Arabia. Despite the growing adoption of e-learning in nursing education, no context-specific, expert-validated module exists for critical care pain management in this context.Purpose: This study aimed to develop and content-validate a context-specific e-learning module on pain management to enhance critical-care nurses’ competency in a regional health cluster in Saudi Arabia.Methods: A three-round modified Delphi technique was employed. An initial needs assessment was conducted through a literature review and expert focus group input. It was then refined over three rounds with a panel of five multidisciplinary critical care specialists with 7 to 23 years of experience. Experts rated content relevance on a four-point scale. Content validity was assessed using the Content Validity Ratio (CVR) and the Content Validity Index (CVI), with retention thresholds set at CVR ≥ 0.99 and I-CVI ≥ 0.80.Results: The Delphi process achieved 100% of retention across all rounds. Of the 25 initial content items, 24 met the CVR and I-CVI cutoffs (CVR = 1.00, I-CVI = 1.00) and were retained. One item, “Non-pharmacological interventions” (CVR = 0.60), was excluded. The final curriculum comprised six modules totaling 2.5 hours, covering pain basics and assessment; clinical aspects of pain; pharmacological management; interdisciplinary practice; case-based application; and assessment of knowledge and skills. New items suggested by the experts and included in the final curriculum were risk stratification, complication monitoring, and documentation protocols. The final scale-level CVI was 1.00.Conclusion: This Delphi study produced an expert- and content-validated e-learning module on critical care pain management. Although strong content validity was established, the small panel size and single-region representation limit generalizability. Following pilot testing and outcome evaluation, this e-module could be used as an effective educational intervention to improve knowledge and potentially clinical practice related to pain management.